Peran Sistem Informasi Akuntansi dalam Peningkatan Penjualan Produk Fashion di PT. Hindo - Erika Floretta Afriana; Fitri Komariyah (PUTRA JAWA PUBLISHER, 2024)
This study aims to determine the role of Accounting Information Systems (AIS) in increasing sales of fashion products at PT Hindo through the B2C (business to customer) system. In this digitalisation era, the use of AIS is very important for companies to improve operational efficiency and effectiveness, including in the sales process. AIS enables better data integration, more accurate sales tracking, and faster and more precise decision making. The research method used is descriptive analysis with a case study approach at PT Hindo. Data were collected through interviews, observations, and analysis of company documents. The results showed that the implementation of AIS at PT Hindo contributed significantly to the increase in sales. This can be seen from the increased accuracy of sales data, efficiency in the reporting process, and the company's ability to respond to market needs more quickly. The conclusion of this study is that AIS has an important role in supporting the increase in sales of fashion products at PT Hindo. AIS not only helps in managing sales data, but also provides analytical tools that allow management to identify market trends and create more effective marketing strategies.